Understanding global development research fieldwork issues, experiences and reflections - Crawford, Gordon 1952-; Kruckenberg, Lena J.; Loubere, Nicholas; Morgan, Rosemary (Scientist); Seaman, Jai (SAGE, 2017)
Built around interviews and personal field notes of authorities and researchers, which really help readers to see what actually happens during field work, this exciting new book gives practical advice on the key aspects of doing developmental fieldwork. A must read for all students, researchers and aid workers contemplating field work in emerging economies. -- Admos Chimhowu This is an up-to-date, thought-provoking and well-balanced publication that brings together the best insights of leading and young scholars at the nexus of development and participatory field research. Its relational, ethics- and power-sensitive perspective makes this book special.--Provided by Publisher.